2003
DOI: 10.1029/2002jd002378
|View full text |Cite
|
Sign up to set email alerts
|

Interannual and seasonal variability of biomass burning emissions constrained by satellite observations

Abstract: We present a methodology for estimating the seasonal and interannual variation of biomass burning designed for use in global chemical transport models. The average seasonal variation is estimated from 4 years of fire‐count data from the Along Track Scanning Radiometer (ATSR) and 1–2 years of similar data from the Advanced Very High Resolution Radiometer (AVHRR) World Fire Atlases. We use the Total Ozone Mapping Spectrometer (TOMS) Aerosol Index (AI) data product as a surrogate to estimate interannual variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
797
5
10

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 674 publications
(873 citation statements)
references
References 87 publications
42
797
5
10
Order By: Relevance
“…Biomass burning is anticorrelated with precipitation, reinforcing the land NPP driven response to ENSO. Modeled global IAV in natural biomass burning agrees with Langenfelds et al [2002] and Duncan et al [2003] in predicting maxima and minima emissions in years 1994/1995 and 1995/1996, respectively. Extremely high emissions in 1997/1998, largely associated with fires in southeast Asia [van der Werf et al, 2003], are not captured by LPJ.…”
Section: Tropical and Southern Hemisphere Fluxessupporting
confidence: 50%
“…Biomass burning is anticorrelated with precipitation, reinforcing the land NPP driven response to ENSO. Modeled global IAV in natural biomass burning agrees with Langenfelds et al [2002] and Duncan et al [2003] in predicting maxima and minima emissions in years 1994/1995 and 1995/1996, respectively. Extremely high emissions in 1997/1998, largely associated with fires in southeast Asia [van der Werf et al, 2003], are not captured by LPJ.…”
Section: Tropical and Southern Hemisphere Fluxessupporting
confidence: 50%
“…The TOMS project has produced the longest available global record of aerosol observations in terms of AI, and a number of studies have demonstrated its feasibility and success (e.g., Torres et al 1998;Chiappello et al 1999;Hsu et al 1999;Cakmur et al 2001;Prospero et al 2002;Duncan et al 2003). Monthly data on a 1.25°ϫ 1°grid are available on the TOMS Web site (http://toms.gsfc.nasa.gov/aerosols/aerosols_v8.html).…”
Section: Data and Analysismentioning
confidence: 99%
“…Much of the biofuel is used for cooking which has no Charcoal only includes the amount of charcoal combusted, not amount of wood to make charcoal. YEVICH AND LOGAN: BIOFUEL AND WASTE BURNING seasonal pattern; trace gases from this burning are emitted throughout the year in contrast to other types of biomass burning which tend to follow seasonal patterns [Duncan et al, 2003].…”
Section: Biofuels Combustionmentioning
confidence: 99%
“…For the Northern Hemisphere, these would be February through early May and end September through mid November, the actual timing depending on latitude, altitude, type of crop and year-specific meteorology. More information on seasonality of this and other types of biomass burning is given by Duncan et al [2003].…”
Section: Emissions From Burning Residue In the Fieldsmentioning
confidence: 99%